Eliminating HPV DNA Positive Result with Large Loop Excision of the Transformation Zone (LLETZ)/Loop Electrosurgical Excision Procedure (LEEP) in Precancerous Cervical Lesions - Sanif, Rizal; Agustiansyah, Patiyus; Nurwany, Raissa; Sastradinata, Irawan; Theodorus; Agustian, Wisman (Indonesian Socety of Obstetrics and Gynecology, 2024)
Abstract Objective: To determine the use of LLETZ/LEEP to eliminate HPV DNA positive result in patients with cervical precancerous lesions at General Hospital dr. Mohammad. Hoesin, Palembang. Methods: A case series with cervical precancerous lesions was undertaken at the Oncology Polyclinic of dr.Mohammad Hoesin Hospital Palembang from January to October 2022. There were 24 samples with positive HPV DNA before LLETZ/LEEP. Samples then checked for HPV DNA after LLETZ/LEEP. The effectiveness of LLETZ/LEEP therapy was analyzed using the Mc Nemar test. Comparison of HPV DNA outcomes (positive or negative) based on procedure, HPV DNA type and histopathological type was analyzed using Fisher Exact and Pearson Chi Square tests. All data were analyzed using SPPS version 22.0. Results: In this study, it was found that the average age of patients with cervical precancerous lesions was 40.25 ± 7.67 years (28 - 57 years). Based on the diagnosis, 8 samples were found with High-grade Squamous Intraepithelial Lesion (HGSIL) and 16 samples with Low-grade Squamous Intraepithelial Lesion (LGSIL). All samples in this study were housewives and the majority were multiparas (75.0%). History of abortion in the patients in this study was only found in 5 samples (20.8%). The results showed that there were significant differences in the HPV DNA before and after LLETZ/LEEP therapy (p = 0.000). In addition, the results showed that there was no difference in the outcome of HPV DNA based on the procedure (p = 1.000) and the type of HPV DNA (p = 0.643). After LLETZ/LEEP therapy was carried out, it was found that only 1 subject has positive HPV DNA result and the HPV DNA virus found was type 52 and (high risk) and 42 (low risk). Conclusion: It can be concluded that LLETZ/LEEP therapy is effective in eliminating HPV DNA positive results in cervical precancerous lesions Keywords: cervical cancer, HPV DNA, LLETZ/LEEP, precancerous lesions, RCT